The Influence of Fable Fairytale and Listening Ability Into Young Children Students’ Speaking Skill of Sleman Yogyakarta - Nada Salwa; Harun Harun; Hully Hully (Yayasan Adra Karima Hubbi, 2024)
Language skills are not separate from the four components of language itself: listening, speaking, pronouncing, and writing. And one of the efforts in improving the ability of fable storytelling for young students can be done by speaking and listening skills. The study aims to test the influence of fable storytelling and fictional abilities on speaking B-class of young children of the sleman district. The research method used is quantitative research of the causality type using ex post facto research methods. The research was carried out on five districts in the district of Sleman, which are: Tempel, Godean, Mlati, Ngaglik, and Prambanan. Total samples are 202 children, with proportional sampling tehnique. Data collection techniques using angket via google form. Data analysis techniques using multiple regression analysis with SPSS 27. The results of the study show that (1) the fable ability variable (X1) has a positive and significant influence with t counting 6.077 and p-value 0,000 against speaking (Y); (2) the speech variable(X2) has a significant influency with t-counting 12.985 and p –value 0,000 against speech (Y); (3) the fairy tale ability variables (X1) and speech capacity (X2) jointly have a positive influence and significance with F- counting 679.297 and a speech p-valuation 0,000. (Y)